Comparative studies on small scale fermentation of cocoa using Acetobacter xylinum and Saccharomyces cerevisiae (wild strain) - Othman Abdul Samah (Persatuan Biokimia Malaysia, 2013)
Cocoa fermentation were carried out under three different controlled treatment using pure cultures of Acetobacter xylinum, Saccharomyces cerevisiae (wild strain) and mixed cultures. A true correlation between acidification, temperature and development of flavour potential during fermentation can be demonstrated in principle. Fermented beans inoculated with A. xylinum and S. cerevisiae (wild strain) showed the potential to improve the flavour of Malaysian cocoa beans as it bring closer to that of the Ghanian control. Of the three treatments, beans inoculated with A. xylinum (pH 5.33) was consistently closer to Ghanian beans (pH 5.84) and was therefore selected as the most appropriate for treatment during fermentation. However random sensory test on all of the samples showed a weak cocoa flavour compared to Ghanian control beans due to relatively strong acidification, bitterness and astringency.